IMPLEMENTATION OF THE ABC-VEN METHOD IN INVENTORY MANAGEMENT OF A WOOD SUPPLIER COMPANY (CASE STUDY: UD PUTRA MULIA) - Mayasari, Sri; Oktyajati, Nancy; Purwati, Sri; Muhammad, Gunawan (Jurnal Disprotek, 2025)
Inventory control is a crucial aspect for timber supply companies such as UD Putra Mulia to avoid the risks of stockouts, delivery delays, and excessive storage costs, as well as to ensure smooth operations and customer satisfaction. The objective of this study is to formulate an optimal inventory control strategy for raw timber materials to minimize the risk of stockouts, avoid excessive storage costs, and improve operational efficiency. Inventory management using the ABC-VEN method is a strategic approach that combines ABC analysis and VEN classification (Vital, Essential, and Non-essential) to enhance efficiency and accuracy in managing stock items. The ABC method prioritizes items based on their material value, while the VEN method classifies items based on their operational importance. The results of this study classify products based on sales value (classes A, B, and C) and their criticality to sales (classes V, E, and N), resulting in nine ideal inventory categories. There are 7 products in the AV category, 2 in AE, 12 in BE, 1 in CE, and 56 in CN. The optimal order quantity (EOQ) is 41 units, safety stock (SS) is 63 units, and the reorder point (ROP) is 57 units. These results indicate that the ABC-VEN approach, along with the calculation of EOQ, SS, and ROP, is effective in supporting more efficient inventory control at UD Putra Mulia.IMPLEMENTASI METODE ABC-VEN DALAM MANAJEMEN PERSEDIAAN PERUSAHAAN PEMASOK KAYU(STUDI KASUS : UD PUTRA MULIA)Pengendalian persediaan merupakan aspek krusial bagi perusahaan suplai kayu seperti UD Putra Mulia untuk menghindari risiko kehabisan stok, keterlambatan pengiriman, dan pemborosan biaya penyimpanan, serta menjaga kelancaran operasional dan kepuasan pelanggan. Tujuan dari penelitian ini adalah untuk merumuskan strategi pengendalian persediaan bahan baku kayu yang optimal guna meminimalkan risiko kehabisan stok, menghindari pemborosan biaya penyimpanan, dan meningkatkan efisiensi operasional. Manajemen persediaan dengan metode ABC-VEN merupakan pendekatan strategis yang menggabungkan analisis ABC dan VEN (Vital, Essential, dan Non-essential) untuk meningkatkan efisiensi dan ketepatan dalam mengelola stok barang. ABC memprioritaskan barang berdasarkan nilai materi, sedangkan VEN mengklasifikasikan barang berdasarkan kepentingan operasional. Hasil dari penelitian ini adalah mengklasifikasikan produk berdasarkan nilai penjualan (kelas A, B, C) dan tingkat kekritisannya terhadap penjualan (kelas V, E, N), sehingga menghasilkan sembilan kombinasi kelas persediaan yang ideal. Kategori AV terdapat 7 produk, kategori AE terdapat 2 produk, kategori BE 12 produk, CE terdapat 1 produk dan kategori CN terdapat 56 produk. Jumlah pesanan optimal dengan nilai EOQ yaitu 41 unit, safety stock 63 unit dan reorder point 57 unit. Hasil ini menunjukkan bahwa pendekatan ABC-VEN serta perhitungan EOQ, SS, dan ROP efektif dalam mendukung pengendalian persediaan yang lebih efisien di UD Putra Mulia.